PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS SMP NEGERI 18 PALU - Riandhana, Taufiq Eka; Ashad, Ashad; Hauris, Hauris; Kulyawan, Roy; Halifah, Nur; Efendi, Efendi (SINERGI : Jurnal Riset Ilmiah, 2025)
Taufiq Eka Riandhana, Nur Halifah, Efendi, Ashad, Hauris, 2025. The Effect of Motivation on Learning Achievement of Class XI Social Studies Students at SMP Negeri 18 Palu. The purpose of the study was to obtain information about whether there is an influence of motivation on student achievement in class XI I IPS in SMP Negeri 18 Palu. The method used is a quantitative descriptive method. The population is 133 students at SMP Negeri 18 Palu. The number of research samples as many as 57 people using the Proportional Sampling technique. The data collection technique used a Likert scale model questionnaire, Observation, Interview and Documentation. Data analysis techniques are first to reduce data, present data, and draw conclusions. The results showed that the results of the analysis of the implications of motivation research on learning achievement had a significant effect on increasing students' learning motivation. The motivation of students at SMP Negeri 18 Palu Class XI IPS can be said to be good with a percentage of 63.44%. The motivation that arises in students cannot be separated from the teacher himself. A student learns because it is driven by mental strength in the form of desire, attention, will, or ideals, and this mental strength can be classified as low and high depending on the teacher's efforts to encourage students and give awards so that students feel able to become even better.